Microengineered hollow graphene tube systems generate conductive hydrogels with extremely low filler concentration - Arndt, Christine; Hauck, Margarethe; Wacker, Irene; Zeller-Plumhoff, Berit; Rasch, Florian; Taale, Mohammadreza; Nia, Ali Shaygan; Feng, Xinliang; Adelung, Rainer; Schröder, Rasmus R.; Schütt, Fabian; Selhuber-Unkel, Christine (Nano letters, 2021)
The fabrication of electrically conductive hydrogels is challenging as the introduction of an electrically conductive filler often changes mechanical hydrogel matrix properties. Here, we present an approach for the preparation of hydrogel composites with outstanding electrical conductivity at extremely low filler loadings (0.34 S m-1, 0.16 vol %). Exfoliated graphene and polyacrylamide are microengineered to 3D composites such that conductive graphene pathways pervade the hydrogel matrix similar to an artificial nervous system. This makes it possible to combine both the exceptional conductivity of exfoliated graphene and the adaptable mechanical properties of polyacrylamide. The demonstrated approach is highly versatile regarding porosity, filler material, as well as hydrogel system. The important difference to other approaches is that we keep the original properties of the matrix, while ensuring conductivity through graphene-coated microchannels. This novel approach of generating conductive hydrogels is very promising, with particular applications in the fields of bioelectronics and biohybrid robotics.
Gesehen am 28.07.2021